Morphology of Ormu’s Folktale (The Study of Propp Theory) - Ummu Fatimah Ria Lestari (Multilingual, 2013)
This research discusses about morphology of Ormu’s folktale which is based on Propp theory. This research used qualitative method. On the other part, it used descriptive-analytics method. In social research, that methods can draw fact and the characters of research population factually and accuracy. Then, they had been analyzed based on analytic methods. In its techniques, the researcheranalyzed its morphology in Ormu’s folklore “Asal Mula Kedatangan Suku Norotoy di Kampung Ormu” so the next step is the application of Structural theory of Vladimir Propp. There are morphology of this folktale consist of 1) eight functions, 2) two pattern naratology, 3) the good value, and 4) two mean protagonist actors, as the result of the study.